Growth conditions that increase or decrease lifespan in Saccharomyces cerevisiae lead to corresponding decreases or increases in rates of interstitial deletions and non-reciprocal translocations. Issue 1 (December 2016) - Maxwell, Patrick
Abstract Background Accumulation of DNA damage, mutations, and chromosomal abnormalities is associated with aging in many organisms. How directly various forms of genomic instability contribute to lifespan in different aging contexts is still under active investigation. Testing whether treatments that alter lifespan change mutation rates early during lifespan could provide support for genomic instability being at least partly responsible for changes in the rates of aging. Results Rates of mutations, direct repeat recombination, or retrotransposition were measured in young cell populations from two strain backgrounds ofSaccharomyces cerevisiae exposed to several growth conditions that shortened or extended yeast chronological lifespan. In most cases, rates of genomic instability did not consistently increase in young cells exposed to lifespan-shortening conditions or decrease in young cells exposed to lifespan-extending conditions. The mutation rate for a copy of theCAN1 gene integrated onto the right arm of chromosome VIII did show expected increases or decreases in young cells in the lifespan-altering growth conditions. These mutations were determined to frequently result from non-allelic recombination events, including non-reciprocal translocations, and were more strongly stimulated by using hydroxyurea to induce DNA replication stress than by the general DNA-damaging agent methyl methanesulfonate. Conclusions The results are not consistent with changes in mutation rates in general mediating the influence of alternative growth conditions on yeast lifespan. The strong correlation between non-allelic recombination events and the effects of the alternative growth conditions on lifespan indicates that genomic instability due to changes in recombination rates may directly contribute to the rate of aging or that lifespan-altering treatments may consistently increase or decrease DNA replication stress. These results further support the connection between DNA replication stress and aging observed in multiple organisms. Chromosomal abnormalities that likely arise from recombination events are more prevalent in multiple human tissues with increasing age, and further work in yeast could help to define mechanisms responsible for this observation and the impact of chromosomal abnormalities on aging.